2020
DOI: 10.7831/ras.8.0_58
|View full text |Cite
|
Sign up to set email alerts
|

Common Strategies to Control <i>Pythium</i> Disease

Abstract: Pythium species are soil-borne pathogens which can cause serious economic loss worldwide and threatening agricultural production. Traditional management methods like chemical fungicides are effective against Pythium spp. But as people pay more attention to human health and environmental issues, alternative methods that are ecofriendly and harmless to health are urgently needed. Currently, various approaches had been made including using natural extract, regulating planting conditions, using plant growthpromoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Moreover, the survival rate was increased by 60% in sepsis-induced model. It has also been reported that cq-9 has antimicrobial activity against Phythium graminicola [ 63 ], which causes severe damage in rice seedlings [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the survival rate was increased by 60% in sepsis-induced model. It has also been reported that cq-9 has antimicrobial activity against Phythium graminicola [ 63 ], which causes severe damage in rice seedlings [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Control of this pythium complex is difficult due to the interwoven nature of many species. Damping-off can be controlled using integrated disease management strategies involving cultural, biocontrol and host-resistance breeding [ 39 , 143 , 144 ]. For cultural management practices, it is important to avoid poorly drained soils, maintain good soil health, good tillage, and use disease-free seeds [ 133 , 144 ].…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
“…Damping-off can be controlled using integrated disease management strategies involving cultural, biocontrol and host-resistance breeding [ 39 , 143 , 144 ]. For cultural management practices, it is important to avoid poorly drained soils, maintain good soil health, good tillage, and use disease-free seeds [ 133 , 144 ]. Biological control using rhizobium strains has been shown to offer protection against pythium damping-off in pea [ 84 ].…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Being fast growing and soilborne in nature, this pathogen is very difficult to manage. [1][2][3][4][5] Banning of many effective chemical fungicides is adding to the complexity, with no viable alternative being available. We have a programme on developing effective biological control strategies for this plant pathogen, using microbial inocula.…”
Section: Introductionmentioning
confidence: 99%